2002
DOI: 10.1021/tx020020+
|View full text |Cite
|
Sign up to set email alerts
|

NMR-Based Metabonomic Studies on the Biochemical Effects of Commonly Used Drug Carrier Vehicles in the Rat

Abstract: The biochemical effects of a series of commonly used drug carrier vehicles were investigated using (1)H NMR spectroscopic and pattern recognition based metabonomic analysis. Animals were treated by oral gavage with six dosage vehicles: 0.5% (w/v) sodium carboxymethylcellulose/0.2% (v/v)tween; microemulsion (consisting of propylene glycol, ethanol, cremophor, and corn oil glycerides); labrafil [consisting of poly(ethylene glycol) 300 esterified with oleic acid] (30%)/corn oil (70%); 0.1 M sodium phosphate buffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(35 citation statements)
references
References 21 publications
2
32
1
Order By: Relevance
“…However, drug vehicle was detected in the fecal profiles on day 1 from both groups and was eliminated within 48 h. Certain drug vehicles have been shown to effect urinary biochemical profiles. However, in a study conducted by Beckwith-Hall et al 36 Tween exerted the smallest effect on the metabolic profiles after saline consistent with the present study. 36 The spectral regions affected by the vehicle were removed from the data set prior to mathematical modeling to minimize its effect on data analyses and interpretation of the metabolic data.…”
Section: Discussionsupporting
confidence: 93%
“…However, drug vehicle was detected in the fecal profiles on day 1 from both groups and was eliminated within 48 h. Certain drug vehicles have been shown to effect urinary biochemical profiles. However, in a study conducted by Beckwith-Hall et al 36 Tween exerted the smallest effect on the metabolic profiles after saline consistent with the present study. 36 The spectral regions affected by the vehicle were removed from the data set prior to mathematical modeling to minimize its effect on data analyses and interpretation of the metabolic data.…”
Section: Discussionsupporting
confidence: 93%
“…Spectra were Fourier transformed, phase-and baseline-corrected using XWINNMR (Bruker, Karlsruhe, Germany), and reduced to 256 integrated regions of equal width (0.04 ppm) using the AMIX (Analysis of MIXtures) software package (version 2.5, Bruker BioSpin GmbH, Rheinstetten, Germany,). Metabolite assignments were made on the basis of previous literature data ( Beckwith-Hall et al 1998;Beckwith-Hall et al 2002) and in certain cases confirmed by spiking. Spectral regions corresponding to drug carrier vehicles, drug metabolites, or parent compound were removed from the analysis.…”
Section: H Nmrmentioning
confidence: 99%
“…Of the analytical techniques used, 1 H-NMR spectroscopy has been shown to be the main metaboliteprofiling tool, as it enables many endogenous metabolites to be quantified rapidly and reproducibly without derivatization or separation (1)(2)(3)(4)(5). The NMR-generated metabolic datasets can be effectively interpreted and classified by the application of multivariate statistical analysis including pattern-recognition methods, such as principal components analysis (PCA) and partial least-squares (PLS) discriminate analysis (1,(5)(6)(7)(8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%